An Advances Study Approach to Calculation of Proposed Recruitment by Clinical Sites on Stage of Feasibility to Clinical Trial of II – III Phases - Svyatoslav Milovanov (Issues and Development in Health Research Vol. 4, 2021)
Annotation: Many of clinical trials failed due to absence of needed per protocol recruitment of patients. Recruitment of patients in centralized trials is announcing by PI of clinical sites during the feasibility stage. This is subjective decision of investigator based on integral approach like experience, incidence of disease and many other parameters. The objective approach like calculation is apparently needed for calculation of proposed recruitment on the stage of feasibility. Materials and Methods: retrospective analysis data of four clinical trials II-III phases, conducted since 2007 to 2017 years. Study Objectives: to find out the approach for calculation of proposed by sites the recruitment on particular study on the satge of feasibility. Statistical Analysis: data had been collected from feasibility questionnaires, open statistical sources. Results: It was proposed the formula for calculation of proposed recruitment of patients on the stage of feasibility. Discussion: Recruitment of patients might be calculated which will decrease the number of failed clinical trials. We called the calculation “Calculated proposed recruitment of patients” - CPRP».